Predicting 3D forces of disc tool and soil disturbance area using fuzzy logic model under sensor based soil-bin - Chandio, Farman Ali; Li, Yaoming; Xu, Lizhang; Ma, Zheng; Ahmad, Fiaz; Cuong, Do Minh; Lakhiar, Imran Ali (International Journal of Agricultural and Biological Engineering, 2020)
A knowledge-based fuzzy logic model was developed on experimental data and used to predict the draft, side and vertical forces and soil disturbance area by disc tillage tool operation. The laboratory research work was conducted to evaluate the performance of the disc tool at three working speeds (1.25 m/s, 1.98 m/s and 2.47 m/s, respectively) and depths (0-5 cm, 5-10 cm and 10-15 cm, respectively) on paddy soil under soil-bin environment. Further, draft (Fx), side (Fz) and vertical (Fy) forces of disc and soil disturbance area were assessed and predicted towards working speeds and depths. A fuzzy prediction model with two input variables (speed and depth) and four output variables was developed and the Mamdani inference approach was used. Draft, side and vertical forces of disc and soil disturbance area were positively responded 0.97, 0.95 and 0.84 and 0.99, respectively. The prediction results showed a close relationship between measured and predicted data. Similarly, the measured and predicted results revealed that the draft, side, vertical forces, and soil disturbance area slightly increased, while increasing the speed and depth of the disc tool. Furthermore, disc forces and soil disturbed area were highly significant (p<0.05) for higher speed towards depth. It was concluded that the fuzzy model may be introduced for predicting the disc forces and soil disturbance area during the disc tillage tool operation with high accuracy. Keywords: disc tillage tool, ANN fuzzy model, 3D forces, sensor, soil bin, soil disturbance area DOI: 10.25165/j.ijabe.20201304.5115 Citation: Chandio F A, Li Y M, Xu L Z, Ma Z, Ahmad F, Cuong D M, et al. Predicting 3D forces of disc tool and soil disturbance area using fuzzy logic model under sensor based soil-bin. Int J Agric & Biol Eng, 2020; 13(4): 77–84.